Cloud Computing in Industries: An Evaluation Regarding Cost and Security - Alabdulrahman, Rawan; ., . (International Journal of Engineering and Technology, 2018)
In this study, the companies which their data being handled by external parties has investigated and the parameter of cost as well as security have been considered. Moreover, an over view has been presented as to analysing the cost reduction and security of data. In this regard, cloud computing in industry has been introduced so that internet-based access to different computing resources such as software, platforms, and infrastructure provided to be facilitates. Adapting the method of cloud computing, Companies put faith and trust into a third party to handle the companyâ€™s electronic-based services, where security might poses as a concern.Â In conclusion, Companies can be then free from IT related matters and focus on the business productivity. Additionally,Â it has been proved that, in this case the benefits outweigh the security and privacy. Therefore, this essay recommends industries, particularly new SMEs, to utilize and benefit from Cloud Computing. However, this essay discussed only the cost and security factors more research should be done on evaluating other aspects that might concern industries such as Cloud Computing performance.Â